Hand and foot syndrome secondary to capecitabine - Narasimhan, Murali; Kumar, Abhishek; Ramakrishnan, Ramachandran (International Journal of Research in Dermatology, 2020)
Hand and foot syndrome are an adverse effect often seen with chemotherapy or with the use of biologics. It is characterised by painful erythema and edema, dry or moist desquamation of palms and soles in mild to moderate case. Severe cases usually present with cracking, peeling, blister, ulcer and severe pain. Here we report a 65-year-old woman with breast carcinoma who was on treatment with capecitabine and presented with fissuring and bleeding over palms and soles, with progressive burning sensation. On examination, hyperpigmentation and scaling were also noted over both palms and soles. She was diagnosed with hand and foot syndrome and was treated with emollients, antibiotics and topical steroids.